Prenatal exposure to bisphenol A and phthalates and behavioral problems in children at preschool age: the Hokkaido Study on Environment and Children's Health - Machiko Minatoya; Sachiko Itoh; Keiko Yamazaki; Atsuko Araki; Chihiro Miyashita; Naomi Tamura; Jun Yamamoto; Yu Onoda; Kazuki Ogasawara; Toru Matsumura; Reiko Kishi (Komiyama Printing Co. Ltd, 2018)
Abstract Background Studies reported adverse behavioral development including internalizing and externalizing problems in association with prenatal exposure to bisphenol A (BPA) and phthalates; however, findings were not sufficient due to using different assessment tools and child ages among studies. This study aimed to examine associations between maternal serum levels of BPA and phthalate metabolites and behavioral problems at preschool age. Methods The Strengths and Difficulties Questionnaire (SDQ) was used to assess behavioral problems at 5 years of age. BPA and phthalate metabolite levels in the first trimester maternal serum was determined by LC-MS/MS for 458 children. Variables used for adjustment were parental ages, maternal cotinine levels, family income during pregnancy, child sex, birth order, and age at SDQ completed. Results The median concentrations of BPA, MnBP, MiBP, MEHP, and MECPP, primary and secondary metabolites of phthalates, were 0.062, 26.0, 7.0, 1.40, and 0.20 ng/ml, respectively. MECPP level was associated with increase conduct problem risk (OR = 2.78, 95% CI 1.36-5.68) overall and the association remained after child sex stratification, and odds ratios were increased with wider confidence interval (OR = 2.85, 95% CI 1.07-7.57 for boys, OR = 4.04, 95% CI 1.31-12.5 for girls, respectively). BPA, ∑DBPm (MnBP + MiBP), and ∑DEHPm (MEHP+MECPP) levels were not associated with any of the child behavioral problems. Conclusions Our analyses found no significant association between BPA or summation of phthalate metabolite levels and any of the behavioral problems at 5 years of age but suggested possible association between MECPP levels and increased risk of conduct problems.